Polymorphism and Association of the Novel KCTD2 Gene with Flavor and Odor in Indonesian Local Sheeps - Herpina Herpina; Kasita Listyarini; Cece Sumantri; Katrin Roosita; Asep Gunawan (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
A candidate marker that influences the flavor and odor of Indonesian sheep that is the Potassium Channel Tetramerization Domain Containing 2 (KCTD2) gene. This study aims to examine the polymorphism and association between the KCTD2 gene and lamb flavor and odor in Indonesian local sheeps. This study used DNA taken from the longissimus dorsi (LD) muscle of 100 rams including 75 Javanese Thin-Tail sheep (JTTS), 10 Javanese Fat-Tail Sheep (JFTS), and 15 Jonggol Sheep (JS), with ranged in weight from 20 to 35 kg and were 10 to 12 months old. The PCR-RFLP technique and GLM test analysis were used to identify polymorphisms and association of KCTD2 gene. The restriction enzyme BafI digests the PCR-RFLP product of the KCTD2 gene. The results showed that the KCTD2 gene was polymorphic (CC and CT). KCTD2 gene analysis showed a significant (P<0.05) association with 3-Methylphenol (MP). This research provide information regarding the role of the KCTD2 gene in lamb flavor and odor, especially in 3-Methylphenol (MP) compounds, and explain KCTD2 as a functional gene in the selection of premium sheep with low flavor and odor in lamb meat.